The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3109/00207454.2015.1135334
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of cerebrospinal fluid S100B are associated with brain injury and unfavorable outcomes in children with central nervous system infections

Abstract: This study has demonstrated that elevated levels of CSF S100B are associated with brain injury and could be used as an independent predictor of clinically unfavorable outcomes at discharge in children with CNS infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 36 publications
0
10
0
5
Order By: Relevance
“…Концентрация S100B достигала пика через 20 ч после заражения и оставалась высокой на протяжении всего эксперимента [22]. При БГМ у детей концентрация S100B коррелировала с тяжестью течения менингита и была независимым предиктором неблагоприятного исхода [24,25].…”
Section: новые методы диагностики бактериального менингитаunclassified
“…Концентрация S100B достигала пика через 20 ч после заражения и оставалась высокой на протяжении всего эксперимента [22]. При БГМ у детей концентрация S100B коррелировала с тяжестью течения менингита и была независимым предиктором неблагоприятного исхода [24,25].…”
Section: новые методы диагностики бактериального менингитаunclassified
“…Further investigations, however, revealed that S100B in serum or CSF exhibited suboptimal sensitivity and specificity for bacterial meningitis. The highest, but still inconsistent, levels of S100B in CSF and serum were seen in viral encephalitis or in bacterial meningitis complicated by ventriculitis or obvious parenchymal abnormalities on brain imaging (44, 46). While many candidate cytokine and immunologic markers have shown promise as diagnostic tools in small studies, some have demonstrated conflicting findings across studies (Table 1).…”
Section: Cytokine-based Evaluation Of Csfmentioning
confidence: 99%
“…It has been shown that enhancing peptides (EPs) derived from the co-receptor binding region of gp120 could promptly accelerated the formation of amyloid fibrils through the EP-derived nanofibers and significantly enhance HIV-1 infection3940. Recently, Zhang et al demonstrated that α7 nAChR plays a detrimental role in the host defense against CNS inflammation caused by microbial (e.g., meningitic pathogens and gp41) and non-microbial factors (e.g., METH) via the NF-κB signaling pathway12, which may be involved in regulation of the molecular marker (S100B) during various CNS disorders41. Similarly, the current study also showed that nicotine could upregulateα7 nAChR through activation of RAGE and S100B in the dentate gyrus (DG) of the hippocampus upon exposure to gp120, METH or NT in vivo , meanwhile the decrease of α7 nAChR and RAGE alleviated leukocyte (HL60 cell) transmigration across the HBMEC monolayers.…”
Section: Disscussionmentioning
confidence: 99%